The Mutation Ala677→Val in the Methylene Tetrahydrofolate Reductase Gene: A Risk Factor for Arterial Disease and Venous Thrombosis - Arruda, Valder R; von Zuben, Paula M; Chiaparini, Luiz C; Annichino-Bizzacchi, Joyce M; Costa, Fernando F (Thrombosis and Haemostasis, 1997)
Mild hyperhomocysteinemia has been identified as a risk factor for arterial disease and for venous thrombosis. Individuals homozygous for the thermolabile variant of the methylene tetrahydrofolate reductase gene (MTHFR) which results from a common mutation Ala677→Val and is found in 5-15% of the general population, have significantly elevated plasma homocysteine levels and may account for one of the genetic risk factors in vascular disease. We have analyzed the prevalence of MTHFR-T homozygotes in patients with arterial disease or venous thrombosis. We studied 191 patients with arterial disease and 127 individuals with venous thrombosis and compared with 296 unmatched controls. The results showed that there was a high prevalence of homozygotes for the mutated MTHFR-T allele among a group of patients with arterial disease (19%) in the absence of hyperlipoproteinemia, hypertension, and diabetes mellitus when compared to controls (4%), odds ratio of 5.52 (95% C.I., 2.27 to 13.51). The prevalence of homozygotes among patients with venous thrombosis was 11%, odds ratio of 2.93 (95% C.I., 1.23 to 7.01). The risk of venous thrombosis remained high, odds ratio of 2.63, even after we excluded 27 patients with hereditary thrombophilia (e.g. factor V Leiden, dysfibrinogene- mia, deficiency of protein C, protein S, antithrombin III, or factor XII) from the 127 overall cases with venous thrombosis. These data support the hypothesis that being a homozygote for the MTHFR-T is a risk factor for the development of arterial diasease and also for venous thrombosis.